Phoenician memories in Hispania: local pasts, global present - Machuca Prieto, Francisco (My University, 2022)
Traditionally, Spanish historiography has tended to consider the victory of Scipio over the Carthaginians in 206 BCE the end of the deep and long Phoenician presence in Iberia. The result of this interpretation, with exceptions, is a view of the Phoenician past as a slowly changing history truncated suddenly by Rome. However, nowdays we know that the Phoenician communities of the Iberian Peninsula do not disappear after the Roman conquest. The Phoenicians of what is today the southern coasts of Spain continued to shape their own cultural and political destiny despite the powerful impact of the Roman rule. Roman imperialism in Hispania clearly resulted in struggles over territory, sovereignty and cultural identity, but the archaeological and literary evidences points to a reality different than that underlying much of modern narratives of opposition. Usually, those struggles have been conceptualized as Roman versus local identities, but not as a generational choices involving old and new practices. In the case of Phoenician communities, the survival of cultural elements rooted in traditions prior to the arrival of Rome certainly does not indicate an active and hostile resistance to Roman customs. On the contrary, this continuity is seen as a renovation, a way of giving free rein to integration without renouncing the particularities. This phenomenon could be linked to the need for legitimation of the local elites, immersed in a complex game of identitary oppositions and aggregations that held the ideological structures of the rather accommodating imperium romanum concerning the integration of the conquered peoples.
Keywords: España - Historia - <....-0414 (Edad antigua); Guerras púnicas; Civilización romana; Fenicios; Identidad étnica; España - Restos arqueológicos fenicios; Etnicidad; Península Ibérica; Usos del pasado; Imperio romano